Investigating The Implementation Of Facilities Management Strategies Within The Namibian Government - Zimba, Fulata (Department of Construction Economics and Management, 2024)
Research on Facilities Management (FM) indicates that it is able to positively influence the performance and success of organisations in various ways including strategy, culture, resource control, service provision, supply chain management and change management. Although FM has developed as a best practice and evolved into a positive approach to managing the physical environment of organisations, its success is predominantly seen and experienced in the business or private sectors and is reflected in FM research which has little or no focus to broader advances in social and organisational science. The role of FM professionals in Namibia, in both the private sector and within the government, has not been extensively researched. Currently there is no statutory body that regulates the FM profession. Thus, this research will look to add to the existing knowledge base specifically regarding how FM is currently being implemented within Namibian government facilities. Relevant information was obtained from the literature review and a case study methodology was adopted using a single case study because the research topic aims to highlight how FM is currently being executed within the Namibian government, to add to the existing knowledge base within the Namibian context. The case study research was applied to this research qualitative research design, using semistructured interviews, the researcher had a list of different questions covering six focus areas. The researcher used thematic analysis to analyse the qualitative data. Overall, the research indicates that there is systemic failure to maintain and effectively manage existing government infrastructure because FM in Namibia is inefficiently implemented. The analysis of the results identified the following barriers to effective FM namely, lack of funding and resources; lack of strategic plans, including preventative maintenance plans; competing priorities, in particular political agendas that do not align to best practices; poor or no performance management; and poor or no benchmarking. The findings show that there is room for growth and great need to better manage facilities, but it will require a substantial investment in both financial terms and in the upskilling of human capital. Although the outlook is quite negative, there are numerous suggestions made on how to improve.